Online Distance Learning During Covid-19 Pandemic: An Empirical Analysis Over the Students’ Opinions - Topkaya, Özgür; Benli, Abdurrahman; Cerev, Gökçe (İstanbul Üniversitesi, 2021)
The COVID-19 Pandemic has changed areas of societal life to a great extent. Educational fronts are one of them as well. Self-isolation has caused the lock down of educational facilities and it led to the rise of online distance learning worldwide. With its pros and cons this method has been used for more than one year. In this regard, the study used a detailed survey to collect the opinions of Turkish higher education students about the e-learning process during the spring term 2020 when the COVID 19 Pandemic began. For this purpose, 750 surveys were conducted over Google Forms with participant of higher education students from Turkey. The results of the research revealed the following findings. The majority of the participants stated that although distance education had some advantages, it was not a substitute for traditional education, and they could not achieve the same efficiency. The main reasons for this conclusion were inadequate infrastructure, internet access problems and unfair competition caused by the lack of computer hardware, especially in the ongoing education throughout the country. Students also stressed the significance of online education and how it helped them to stick to their academic careers as they had no alternative other than following an online education system in the social isolation period of COVID-19 measures.
Keywords: Sociology; Sosyoloji